2019
DOI: 10.1038/s41467-018-08204-8
|View full text |Cite
|
Sign up to set email alerts
|

Half-quantum vortices and walls bounded by strings in the polar-distorted phases of topological superfluid 3He

Abstract: Symmetries of the physical world have guided formulation of fundamental laws, including relativistic quantum field theory and understanding of possible states of matter. Topological defects (TDs) often control the universal behavior of macroscopic quantum systems, while topology and broken symmetries determine allowed TDs. Taking advantage of the symmetry-breaking patterns in the phase diagram of nanoconfined superfluid 3He, we show that half-quantum vortices (HQVs)—linear topological defects carrying half qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(132 citation statements)
references
References 86 publications
9
120
1
Order By: Relevance
“…1 in Ref. [17]). The combined process in superfluid 3 He (two phase transitions and the intermediate polar phase) is analogous to the spacetime defect of the regularized big bang singularity, which has a vanishing determinant of the spacetime metric.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…1 in Ref. [17]). The combined process in superfluid 3 He (two phase transitions and the intermediate polar phase) is analogous to the spacetime defect of the regularized big bang singularity, which has a vanishing determinant of the spacetime metric.…”
Section: Discussionmentioning
confidence: 91%
“…I. In superfluid 3 He experiments, there occur phase transitions between different topological phases [16,17]. In one of these phases-the polar phase-the determinant of the effective tetrad field vanishes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 discussed by Schwarz [42], who collaborated with Belavin and Polyakov in the instanton problem [43]. Experimentally the halfquantum vortices were observed only 40 years later, first in the time-reversal symmetric polar phase of 3 He [44], and finally in the chiral 3 He-A [45]. Moreover, it was found that they survive the phase transition to 3 He-B, where the half-quantum vortex is topologically unstable: it becomes the termination line of the nontopological domain wall -the analog of Kibble cosmic wall [46].…”
Section: Novikov Topology Alice String Berezinzkiimentioning
confidence: 99%
“…In cosmology, it has been noted that such composite defects can be nucleated through successive phase transitions with different symmetry breaking in grand unification theories; furthermore, composite defect formation has been proposed as a possible mechanism for galaxy formation [1,2] and baryogenesis [3] in the early Universe.Spinful superfluid systems with multiple symmetry breaking provide an experimental platform for studying the physics of composite defects and, thus, to examine the cosmological scenario. In superfluid 3 He-B, it has been observed that a spin-mass vortex, on which a planar soliton terminates, can survive after phase transitions by being pinned on the vortex lattice [4,5] or nafen [6]. Composite defects have also been theoretically studied in the atomic Bose-Einstein condensate (BEC) system.…”
mentioning
confidence: 99%